New-Onset Refractory Status Epilepticus and Febrile Infection-Related Epilepsy Syndrome Cases in Children: A Retrospective Cohort Study in South of Iran - Nemati, Hamid; Modanlou, Atena; Shorafae, Eslam; Taghizade, Razie; Inaloo, Soroor (Iranian Journal of Child Neurology, 2025)
Objectives Epilepsy is one of the most common health problems in Iran. Considering this issue, the present study aimed to investigate New-Onset Refractory Status Epilepticus (NORSE) and Febrile Infection-Related Epilepsy Syndrome (FIRES) cases in children and evaluate the neurological outcome, referring to the special care department of Namazi Hospital, Shiraz, Iran. Materials & Methods Eight hundred seventy-three patients with status epilepticus (SE) referred to the medical centers of Shiraz Medical Sciences University were retrospectively examined from September 2021 to December 2022. After obtaining consent, the patients completed the questionnaire based on the literature review. Research data were collected and analyzed using SPSS version 23 software, t-test, Pearson correlation, and chi-square statistical methods. Results The obtained results revealed that out of 873 patients with SE, 140 patients had inclusion criteria for NORSE and FIRSE (63 had NORSE, and 30 had FIRSE). The developmental status of the patient was good in 26.4% of cases and had minimal complications in 21.4% of cases. Mortality in the studied subjects was 33.6% (47 patients), and seizures were controlled in 63 patients (64.9). Furthermore, the results showed that the cause of epilepsy in 47 people (33.6%) of the investigated people was infection/inflammation. Furthermore, no correlation was observed between the gender and age of the patients and the investigated outcomes (p-value>0.05). Only in seizure control, a significant difference was observed between the females and males (p-value<0.05). Conclusion This study concluded that the rate of NORSE and FIRES in the examined children is high. Moreover, one-third of these patients will not have a chance to survive. The results of the present study emphasize the need for more comprehensive studies in this field